Reaksi Masyarakat terhadap Produk Kepemilikan Logam Mulia (KLM) di BANK Syariah - Heni Pratiwi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
Islamic Banking applies the pattern of gold investment, because of rapid development. This study aims to determine how the public reactions to KLM products in Islamic Banking and what preference drives people react positively or negatively to KLM products in Islamic Banking. This study is a qualitative research and the sampling was purposive sampling method. The data collection techniques is through distributing questionnaires to the respondents. The data analysis technique used is the descriptive statistical analysis techniques and analysis of discrimination. Based on the research results, the public reaction to the KLM product in Islamic Banking known at the high category (positive) with a yield of 72% of the 100 respondents. The results based onfive indicators of reaction, four indicators are at highlevel categories, ie: indicatorsof resources 59%, personal reference indicator 53%, culture indicator 61%, and theindicators of moral, economic, age 56%. While indicators of thoughts and feelingare at a low level category by 51%. Based on the results of discriminant analysis, itis known that the preferences that drive people react positively to KLM products inIslamic Banking are preference personal factors, resources, moral, economic, age,and culture. While the preference that encourage the public to react negatively isthought factor and feeling that on the lowest coefficient of discriminant analysis.